Additional data on the fauna of Psilidae (Diptera) of France, with description of three new species of Chamaepsila and updated keys - Claude, Jocelyn; Tissot, Bruno (Zootaxa, 2023)
Since the first faunistic overview of the Psilidae (Diptera) of mainland France published in 2021 with data up to 2019, new material from 26 natural sites and three collections has been examined by the authors. 2663 specimens collected in continental France were identified, representing 37 species. From this material, three species from three mountain national natural reserves are described as new to science: Chamaepsila withersi sp. nov., Chamaepsila massanea sp. nov. and Chamaepsila ristolasiensis sp. nov. Chamaepsila andreji (Shatalkin, 1996) is mentioned for the first time in France. Keys to the species of Chamaepsila Hendel, 1917 from Europe are updated and provided in English and French. Illustrations of the genitalia of the males of Chamaepsila limbatella (Zetterstedt, 1847) and Chamaepsila strigata (Collin, 1959) are provided for the firt time. Male terminalia of Chamaepsila andreji (Shatalkin, 1996), Chamaepsila bicolor (Meigen, 1826), Chamaepsila ephippium (Zetterstedt, 1847), Chamaepsila luteola (Collin, 1944), Chamaepsila obscuritarsis (Loew, 1856), Chamaepsila quadrilineata (Strobl, 1898) and Chamaepsila villosula (Meigen, 1826) are redrawn from the authors’ material, more complete and more precise. Additional faunistic data are presented for all French species of Psilidae, derived from the 2600+ specimens identified since 2019.